'Landscape of exception': Power inequalities and ethical planning challenges in the landscape transformation of south-eastern Sicily. (February 2022) - Lo Piccolo, Francesco; Todaro, Vincenzo
In some marginal contexts of Southern Italy, in light of specific economic, political and social conditions, certain relationships between 'strong powers' and 'weak powers' produce a suspension of norms/rights that is, paradoxically, 'normalised'. This creates a particular spatial variation of Agamben's (2005) state of exception concept: the 'landscape of exception'. With respect to the possible conditions of 'exception', this article describes the 'landscape of exception' of the greenhouse system in South-Eastern Sicily. This 'landscape of exception' is generated by the greenhouses, in particular those dedicated to vegetable production, through an effective mechanism of spatial manipulation of the landscape and social control of migrant workers. In relation to these considerations, this work reflects on the ethical challenges and responsibilities of planning, highlighting (explicit and latent) conflicts and power inequalities in the 'landscapes of exception', where issues of environmental sustainability, social justice and the suspension of norms are closely intertwined.